Rationalism in politics in the thought of Abu Othman al-Jahez - aldjouzi, Abdelmadjid (Journal of Social Sciences and Humanities, 2021)
In this article, we show aspects of the rationalism in politics of Abu Othman al-Jahez. And his opinions about rationalism in politics can be summed up in the following points: - That political science has its origins and its principles. - That the Imamate is imposed by reason and not by divine law, because it concerns the life of individuals such as the organization of their society, their protection and the prevention of injustice, and for justice to be rendered. - That his vision of the nature of power, as a civil and social nature, and its opposition to what we call today: the rule of divine right or "religious state". - That is his conviction of political realism -a characteristic of rationality-manifested by the fact that it is based on the reality of human nature-the existence and persistence of injustice-to confirm the need permanent naturalness of the Imam. And even at the presence of virtuous imam the imamate of the sub-virtuous imam can be accepted to prevent sedition. And only one imam be established to prevent conflict. And establish it by the elite within the limits of the possible. - That power must serve reason. - And finally, in his call to Islamic nationalist thought and Arab national unity based on objective pillars that transcend different affiliations and realize the spirit of citizenship.